Use of GIS building violations according to structural plans - dwikat, Belal; Yacoub, Osama (جامعة بوليتكنك فلسطين - مساحة, 2021)
This project tried to find the front setback based on the Palestinian building laws of 2011. Because the front setback needs a lot of time and data to find it, the front setback was found depending on the location of the buildings in relation to the roads, and the research aimed to find the setback rate in Nablus, Tulkarm and Dura. The project relied on the applied approach by using GIS techniques, to reach the desired results One of the results of the project was the production of several maps illustrating the role of geographic information systems in saving time and effort to know the size of the violations and to show the forward setback. Forward setback maps and violation maps were produced for buildings that exceeded the required limit, and the project also made several recommendations.
CD, no of pages 104, مساحة 6/2021
Keywords: GIS; building violations